Socio-demographic profile of medical students in Aotearoa, New Zealand (2016-2020): a nationwide cross-sectional study - Bagg, W.; Curtis, E.; Eggleton, K.S.; Nixon, G.; Bristowe, Z.; Brunton, Paul; Hendry, C.; Kool, B.; Scarf, D.; Shaw, S.; Tukuitonga, C.; Williman, J.; et al. (2023)
Objective To determine the socio-demographic profile of all students enrolled to study medicine in Aotearoa New Zealand (NZ). Design and setting Observational, cross-sectional study. Data were sought from the Universities of Auckland and Otago, the two NZ tertiary education institutions providing medical education, for the period 2016-2020 inclusive. These data are a subset of the larger project 'Mirror on Society' examining all regulated health professional enrolled students in NZ. Variables of interest: gender, citizenship, ethnicity, rural classification, socioeconomic deprivation, school type and school socioeconomic scores. NZ denominator population data (18-29 years) were sourced from the 2018 census. Participants 2858 students were enrolled to study medicine between 2016 and 2020 inclusive. Results There were more women (59.1%) enrolled to study medicine than men (40.9%) and the majority (96.5%) were in the 18-29 years age range. Maori students (rate ratio 0.92; 95% CI 0.84 to 1.0) and Pacific students (rate ratio 0.85; 95% CI 0.73 to 0.98) had lower overall rates of enrolment. For all ethnic groups, irrespective of rural or urban origin, enrolment rates had a nearly log-linear negative relationship with increasing socioeconomic deprivation. Enrolments were lower for students from rural areas compared with those from urban areas (rate ratio 0.53; 95% CI 0.46-0.61). Overall NZ's medical students do not reflect the diverse communities they will serve, with under-representation of Maori and Pacific students and students who come from low socioeconomic and rural backgrounds. Conclusions To meaningfully address these issues, we suggest the following policy changes: universities commit and act to Indigenise institutional ways of knowing and being; selection policies are reviewed to ensure that communities in greatest need of doctors are prioritised for enrolment into medicine (specifically, the impact of low socioeconomic status should be factored into selection decisions); and the government fund more New Zealanders to study medicine.